Identification of the Economic Crisis in Indonesia 2019-2022 - Nusantara, Agung; Nawatmi, Sri (Untag Business and Accounting Review, 2022)
This paper aims to to identify when the economic crisis in Indonesia occurred by basing itself on the formulation of The National Bureau of Economic Research, as the economic research authority in the United States, which is used as a reference for many countries including the United Nations. The Holdrick-Prescot Expectation Model is use as model with a de-trending approach that describes the information contained in the data without involving other data that might contribute to the movement of the data. the results of identification using the Gordon model and the Hodrick-Prescott method, it can be seen that the identification of crises is more accurate when using the definition applied by the NBER. Through the definition of the NBER crisis, it can be seen that Indonesia has experienced a decline in actual GDP compared to its trend value since 2019, Q4, which of course indicates the onset of an economic crisis.